Prognostic value of fasting hyperglycemia in patients with COVID-19 – Diagnostic test accuracy meta-analysis. (May 2021) - Handayani, Dewi Ratih; Juliastuti, Henny; Nawangsih, Eka Noneng; Kusmala, Yudith Yunia; Rakhmat, Iis Inayati; Wibowo, Arief; Pranata, Raymond
Abstract: Aims: This meta-analysis aimed to assess the prognostic value of fasting hyperglycemia in patients with COVID-19. Methods: A systematic literature search on PubMed, Embase, and Scopus were performed up until February 18, 2021. Fasting hyperglycemia was defined as fasting plasma glucose level above the reference value. The outcome of interest was poor outcome, which was a composite of mortality and severe COVID-19. The effect estimate was in odds ratio (OR). Results: There were 9045 patients from 12 studies included in this systematic review and meta-analysis. The prevalence of fasting hyperglycemia was 29%. The incidence of poor outcome was 15%. Fasting hyperglycemia was associated with poor outcome in COVID-19 (OR 4.72 [3.32, 6.72], p < 0.001; I 2 : 69.8%, p < 0.001). Subgroup analysis in patients without prior history of diabetes showed that fasting hyperglycemia was associated with poor outcome in COVID-19 (OR 3.387 [2.433, 4.714], p < 0.001; I 2 : 0, p = 0.90). Fasting hyperglycemia has a sensitivity of 0.57 [0.45, 0.68], specificity of 0.78 [0.70, 0.84], PLR of 2.6 [2.0, 3.3], NLR of 0.55 [0.44, 0.69], DOR of 5 [3, 7], and AUC of 0.74 [0.70, 0.78] for predicting poor outcome. In this pooled analysis, fasting hyperglycemia has a 32% post-test probability for poor outcome, and absence of fasting hyperglycemia confers to a 9% post-test probability. Meta-regression and subgroup analysis showed that the sensitivity and specificity varies by chronic kidney disease but not by age, male (gender), hypertension, and chronic kidney disease. Conclusion: Fasting hyperglycemia was associated with mortality in COVID-19 patients, with or without diabetes. Prospero: CRD42021237997. Highlights: Fasting hyperglycemia was associated with poor outcome in COVID-19. Fasting hyperglycemia was associated also with poor outcome in COVID-19 in patients without prior history of diabetes. Fasting hyperglycemia has a 57% sensitivity 78% specificity and AUC of 0.74 for predicting poor outcome. Presence and absence of fasting hyperglycemia resulted in 32% and 9% probability for poor outcome, respectively.